PERAN IRWANDI YUSUF UNTUK PELEMBAGAAN PARTAI NANGGROE ACEH - Nofriadi Nofriadi; Nurmalisa H Chawari (Journal of Political Sphere, 2021)
AbstrakOne of the pillars of democracy is a political party that can lead great people to be able to sit in legislative and executive institutions, political parties are familiar terms in the ears of everyone in the world and from various groups, both politicians, academics, and ordinary people, parties Politics is usually indectric with a group of people who are members of an organization and have the same goal. Aceh's local political parties are regulated in PP No. 20 of 2007. Item 1, Article 2 states: Aceh's local political parties are a group of people who are voluntarily with efforts to realize the desires of people who have aspirations to win candidates both DPRK or DPRA proposed. This research is a qualitative type through literature study. The Institutionalization of the Aceh Nannggroe Party (PNA) has not been going well, it is evident the existence of internal conflicts in the party between the Irwandi Yusuf camp and Samsul Bahri (Tiong) and can be seen the dualism conflict of the management of Nanggroe Aceh Beach (PNA) starts from the Extraordinary Congress (KLB) ) pioneering by Samsul Bahri. Persolistic Irwandi Yusuf determined the victory of the Aceh Nanggroe Party.Keywords: Irwandi Yusuf, PNA, Institutional, Local.